Firm subsidies, financial intermediation, and bank stability - Aleksandr Kazakov; Michael Koetter; Mirko Titze; Lena Tonzer (Tinbergen Institute, 2022)
We use project-level information for the largest regional economic development program in German history to study whether government subsidies to firms affect quantity and quality of bank lending. We combine recipient firms under the Improvement of Regional Economic Structures program (GRW) with their local banks during 1998-2019. The modalities of GRW subsidies to firms are determined at the EU level. Therefore, we use it to identify bank outcomes. Banks with relationships to more subsidized firms exhibit higher lending volumes without any significant differences in bank stability. Subsidized firms, in turn, borrow more indicating that banks facilitate regional economic development policies
Keywords: G21; G28; H25; 330; Government subsidies; Financial intermediation; Bank stability